Study on the outdoor thermal comfort of college students under different activity intensities in a high-altitude climate zone - Zhang, Yingzi; Zhang, Xiaobo; Han, Jiaqin; Liu, Xinxing (Frontiers in Public Health, 2024)
Introduction Research on the outdoor thermal comfort (OTC) of a university campus is beneficial to the physical and mental health of college students. Methods In this study, the OTC of students attending Tibet University in Lhasa, which experiences high-altitude cold climate conditions, under different activity intensities was studied using field measurements and a questionnaire survey. Results With the increase in activity intensity, the comfort physiologically equivalent temperature (PET) value gradually increased in summer, while the comfortable PET value gradually decreased in winter. The most comfortable PET value is 17.6°C in summer and 11.5°C in winter. The neutral PET of Tibetan college students during outdoor activities in summer was 16.3°C, and the neutral PET of outdoor activities in winter was 12.1°C. Gender and ethnicity had different effects on thermal sensation under different activity intensities. Under vigorous-intensity activities, PET in winter and summer had the greatest influence on thermal sensation. The situation was different under moderate-intensity activity. PET had the greatest influence on thermal sensation in summer, and Tmrt had the greatest influence on thermal sensation in winter. Discussion These findings provide a basis for an improved design of the outdoor environment under different outdoor activity intensities in high-altitude areas.